Ideology and State Apparatus to Create New Order State Power - sianipar, jonah silas (HK-Publishing, 2021)
AbstractThis research tries to describe how the New Order State Journey to power and perpetuates its power. By applying Althusser's theory of State Apparatus, this study specifically focuses on the concept of Ideological State Apparatuses (ISA) and Repressive State Apparatuses (RSA) which were operationalized in the New Order society. Qualitative descriptive research is used to interpret data in books that have researched the â€œNew Orderâ€ before. The results of this study indicate that the â€œNew Orderâ€ state used ISAs such as political parties, cultural, law, media, and religion. Then, â€œNew Orderâ€ state used the RSA such as military and para-military organizations to control and maintain domination within the Indonesian State.Keywords: New Order State, Ideological, State ApparatusAbstrakPenelitian ini mencoba mendeskripsikan bagaimana Perjalanan Negara Orde Baru berkuasa dan melanggengkan kekuasaannya. Dengan menerapkan teori Althusser tentang Aparatur Negara, penelitian ini secara khusus berfokus pada konsep Aparatus Ideologi Negara (ISA) dan Aparatur Negara Represif (RSA) yang dioperasionalkan dalam masyarakat Orde Baru. Penelitian deskriptif kualitatif digunakan untuk menafsirkan data dalam buku-buku yang pernah diteliti â€œOrde Baruâ€ sebelumnya. Hasil penelitian ini menunjukkan bahwa negara â€œOrde Baruâ€ menggunakan ISA seperti partai politik, budaya, hukum, media, dan agama. Kemudian, negara â€œOrde Baruâ€ menggunakan RSA seperti organisasi militer dan paramiliter untuk mengontrol dan mempertahankan dominasi di dalam Negara Indonesia.Kata Kunci: Negara Orde Baru, Ideologi, Â State ApparatusÂ